Self-esteem : a proven program of cognitive techniques for assessing, improving, & maintaining your self-esteem - McKay, Matthew; Fanning, Patrick (New Harbinger Publications, 2016)
The much-anticipated fourth edition of the best-selling classic by Matthew McKay, Self-Esteem is the go-to guide for those seeking to increase their sense of self-worth. This fully revised new edition features an innovative application of acceptance and commitment therapy (ACT) to self-esteem and utilizes updated cognitive behavioral therapy (CBT) to help readers create positive change and thrive.